Remediating the Writing Performance of Struggling Writers through a Self-regulated Strategy Development Approach - Rodny Giverson Garcia; Zayda Asuncion (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
This study explored the writing difficulties of struggling writers and attempted to improve their performance in argumentative writing using Self-Regulated Strategy Development approach (SRSD). Using a diagnostic writing test, 39 senior high school students were identified as struggling writers in a secondary school. The participants were involved in a four-week writing intervention. During the process, they were trained to write using two writing strategies. The scoring of the outputs in the diagnostic and post-tests was mediated by two inter-raters following the criteria on writing performance (Jacobs et al., 1981). Initial results showed that struggling writers tend to perform poorly in all areas of writing performance. But after the intervention, the essay of the participants improved in terms of scores and characteristics. The study further explores the activities that worked during the intervention and the perception of participants towards their writing performance. Finally, implications to teaching argumentative writing to struggling writers are provided based on the intervention process.